2023
DOI: 10.1038/s41598-023-43173-z
|View full text |Cite
|
Sign up to set email alerts
|

Real-time detection of road manhole covers with a deep learning model

Dangfeng Pang,
Zhiwei Guan,
Tao Luo
et al.

Abstract: Road manhole covers are crucial components of urban infrastructure; however, inadequate maintenance or poor marking can pose safety risks to vehicular traffic. This paper presents a method for detecting road manhole covers using a stereo depth camera and the MGB-YOLO model. We curated a robust image dataset and performed image enhancement and annotation. The MGB-YOLO model was developed by optimizing the YOLOv5s network with MobileNet-V3, Global Attention Mechanism (GAM), and BottleneckCSP, striking a balance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…Recently, it was reported that the model performance is superior with ultrasound videos compared to static ultrasound images [22]. YOLOv7, used in our study, and the latest version, YOLOv8 [55], are the fastest and most accurate real-time object detection models, which are suitable for multiple object detection from video files in real time. The development of a YOLO-based model that can detect metastatic LNs in real time during US examinations will be one of the most important themes of future research, necessitating multicenter studies with vast quantities of US video data.…”
Section: Discussionmentioning
confidence: 91%
“…Recently, it was reported that the model performance is superior with ultrasound videos compared to static ultrasound images [22]. YOLOv7, used in our study, and the latest version, YOLOv8 [55], are the fastest and most accurate real-time object detection models, which are suitable for multiple object detection from video files in real time. The development of a YOLO-based model that can detect metastatic LNs in real time during US examinations will be one of the most important themes of future research, necessitating multicenter studies with vast quantities of US video data.…”
Section: Discussionmentioning
confidence: 91%
“…For example, Wei et al [11] used a combination of multiple symmetrically arranged cameras and lidars to classify manhole covers through descriptors and support vector machine algorithms. Pang et al [12] proposed a real-time road manhole cover detection method based on deep learning model. By optimizing the network structure and reducing the size of the model and the number of parameters, the effect of deployment on vehicle-mounted embedded devices is achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, deep learning and edge computing have become popular for real-time obstacle detection and tracking, offering improved accuracy. Deep learning models such as YOLO, CNNs, and DSODs are especially noted for their efficacy in aerial vehicle obstacle detection [12,13]. However, the success of these models largely depends on the quality and variety of training data.…”
Section: Introductionmentioning
confidence: 99%